PEREMPUAN SEBAGAI AGEN PENDIDIKAN INFORMAL ANAK DALAM PENGUATAN KARAKTER BERBASIS BUDAYA: STUDI PADA MASYARAKAT ADAT LEGIAN, BALI - Andi Sadriani; Syamsu A Kamaruddin; Arlin Adam; Ahmadin Ahmadin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study is motivated by the importance of strengthening children’s character based on cultural values amid the rapid pace of modernization, which has the potential to erode local values, particularly within Balinese indigenous communities. The focus of this research is to examine the role of women as agents of informal education in strengthening children’s character based on culture in the indigenous community of Legian, Bali. This study employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, involving women (mothers) as primary informants, as well as community leaders and children as supporting informants. Data analysis was conducted interactively through the processes of data reduction, data display, and conclusion drawing, with validity ensured through source and method triangulation. The findings reveal that women play a central role in children’s informal education through habituation, role modeling, communication, and children’s involvement in cultural practices such as preparing banten (ritual offerings), participating in traditional ceremonies, using the Balinese language, and engaging in social activities such as ngayah (communal voluntary service). Women also function as social controllers and facilitators in maintaining the continuity of cultural values amid the influences of modernization. In conclusion, this study affirms that women are key actors in transmitting cultural values and shaping children’s character in a contextual and sustainable manner. Therefore, they make a significant contribution to cultural preservation and the strengthening of the younger generation’s identity.